Three approaches to overcome compartmentalization: A brief epistemological analysis - Gaj, Nicolò (Rivista di Psicologia Clinica - Open Access, 2024)
The authors of the target article (Salvatore et al., 2022) provided an in-depth analysis of the features and the causes of professional psychology’s fragmentation, generally referred to as compartmentalization. The present contribution is a critical reflection on the three approaches aimed at overcoming it. In conclusion, some preliminary remarks are presented regarding the primary components that a theory of practice should encompass.